2004
DOI: 10.1152/ajprenal.00355.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sodium transport antagonism reduces thrombotic microangiopathy in stroke-prone spontaneously hypertensive rats

Abstract: We examined whether amiloride, an agent that possesses epithelial sodium channel (ENaC)- and sodium/hydrogen exchange (NHE)-inhibitory activities, would exhibit renal vascular protection in saline-drinking, stroke-prone spontaneously hypertensive rats (SHRSP). SHRSP received amiloride (1.0 mg.kg(-1).day(-1), n = 6) or deionized water (3 mg.kg(-1).day(-1), n = 6) for 5 wk starting at 61 days of age. Systolic blood pressure (SBP) did not differ among the groups, and there was no difference in the average daily u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In the first experiment, mice (same age, sex, and strain as above) were injected with insulin and 25% dextrose or vehicle (n Ď­ 6/treatment) and urine was collected in metabolic cages (Hatteras Instruments, Cary, NC) for 2.5 h. Three days later, all the mice in the above set were administered benzamil (1.4 mg/kg body wt ip; Sigma, St. Louis, MO), a specific antagonist of ENaC, 30 min following insulin-plus-dextrose or vehicle injections, as above, and then urine was collected for 2.5 h. The 30-min lag period was instituted to allow time for ENaC to be upregulated by insulin before antagonizing its actions. The antinatriuretic response to benzamil has been used as an index of relative ENaC activity (22) and was dosed based on a previously published therapeutic dose (40).…”
Section: Methodsmentioning
confidence: 99%
“…In the first experiment, mice (same age, sex, and strain as above) were injected with insulin and 25% dextrose or vehicle (n Ď­ 6/treatment) and urine was collected in metabolic cages (Hatteras Instruments, Cary, NC) for 2.5 h. Three days later, all the mice in the above set were administered benzamil (1.4 mg/kg body wt ip; Sigma, St. Louis, MO), a specific antagonist of ENaC, 30 min following insulin-plus-dextrose or vehicle injections, as above, and then urine was collected for 2.5 h. The 30-min lag period was instituted to allow time for ENaC to be upregulated by insulin before antagonizing its actions. The antinatriuretic response to benzamil has been used as an index of relative ENaC activity (22) and was dosed based on a previously published therapeutic dose (40).…”
Section: Methodsmentioning
confidence: 99%
“…This test was performed after 7 days on the study. After a 24-h baseline collection of urine in Nalgene metabolic cages (Harvard Apparatus, Holliston, MA), benzamil (0.7 mg/kg body wt) was administered intraperitoneally (ip) in a single injection based on a previously published therapeutic dose (44). Urine was then collected in the following time increments after the injection: 0 -3, 3-6, and 6 -24 h. Urinary sodium was measured by an ionselective electrode system (EL-ISE Electrolyte System, Beckman Instruments, Brea, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in SHRSP using agents that interfere with the renin–angiotensin–aldosterone system have shown a dissociation between BP lowering and protection against salt-sensitive end-organ damage (Stier et al, 1991; Rocha et al, 1998) and have specifically implicated aldosterone as a major factor in the etiology of salt-sensitive kidney damage (Chander et al, 2003). Consistent with a pivotal pathophysiological role of aldosterone in the saline-drinking SHRSP and the ability of aldosterone to stimulate the epithelial sodium channel (ENaC), Sepehrdad et al (2003, 2004) found that amiloride and other agents that inhibit ENaC function offer protective effects against the development of proteinuria and renal microvascular damage. Interestingly, epoxyeicosatrienoic acids (EETs), cytochrome P450 (CYP) epoxygenase metabolites of arachidonic acid, have been shown to directly inhibit ENaC activity (Wei et al, 2004).…”
Section: Introductionmentioning
confidence: 83%